2014
DOI: 10.1523/jneurosci.2441-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Thalamocortical Short-Term Plasticity Elicited by Ongoing Stimulation

Abstract: To produce sensation, neuronal pathways must transmit and process stimulus patterns that unfold over time. This behavior is determined by short-term synaptic plasticity (STP), which shapes the temporal filtering properties of synapses in a pathway. We explored STP variability across thalamocortical (TC) synapses, measuring whole-cell responses to stimulation of TC fibers in layer 4 neurons of mouse barrel cortex in vitro. As expected, STP during stimulation from rest was dominated by depression. However, STP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 83 publications
0
42
0
Order By: Relevance
“…Hence a number of studies also demonstrated strong effects of calcium concentration on STP. In particular studies comparing STP in “classical” in vitro calcium concentration and in in vivo -like calcium concentration showed larger facilitation and/or reduced depression with the later [ 109 , 110 , 135 , 150 , 151 , 154 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence a number of studies also demonstrated strong effects of calcium concentration on STP. In particular studies comparing STP in “classical” in vitro calcium concentration and in in vivo -like calcium concentration showed larger facilitation and/or reduced depression with the later [ 109 , 110 , 135 , 150 , 151 , 154 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…and synapses mediating thalamocortical input can have diverse temporal filtering properties [15]. However, how these capacities relate to sensory sequence learning in a living animal is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Synapses exhibit functional heterogeneity in strength and short-term plasticity (STP; Atwood and Karunanithi, 2002; Dittman et al, 2000; Grande and Wang, 2011; Millar et al, 2002) which are critical for circuit computations (Abbott and Regehr, 2004; Chabrol et al, 2015; Chadderton et al, 2014; Diaz-Quesada et al, 2014). The function of synapses can be quantified using analysis methods based on the quantal theory of transmission (Katz, 1969), where synaptic strength elicited by a single presynaptic AP can be estimated by the product of three parameters: number of release sites (N), the probability that a single vesicle releases neurotransmitter (P v ), and the quantal size (q).…”
Section: Introductionmentioning
confidence: 99%